Nano-scale physical properties characteristic to metastatic intestinal cancer cells identified by high-speed scanning ion conductance microscope. (January 2022) - Wang, Dong; Sun, Linhao; Okuda, Satoru; Yamamoto, Daisuke; Nakayama, Mizuho; Oshima, Hiroko; Saito, Hideyuki; Kouyama, Yuta; Mimori, Koshi; Ando, Toshio; Watanabe, Shinji; Oshima, Masanobu
Abstract: Recent genetic studies have indicated relationships between gene mutations and colon cancer phenotypes. However, how physical properties of tumor cells are changed by genetic alterations has not been elucidated. We examined genotype-defined mouse intestinal tumor-derived cells using a high-speed scanning ion conductance microscope (HS-SICM) that can obtain high-resolution live images of nano-scale topography and stiffness. The tumor cells used in this study carried mutations in Apc (A), Kras (K), Tgfbr2 (T), Trp53 (P), and Fbxw7 (F) in various combinations. Notably, high-metastatic cancer-derived cells carrying AKT mutations (AKT, AKTP, and AKTPF) showed specific ridge-like morphology with active membrane volume change, which was not found in low-metastatic and adenoma-derived cells. Furthermore, the membrane was significantly softer in the metastatic AKT-type cancer cells than other genotype cells. Importantly, a principal component analysis using RNAseq data showed similar distributions of expression profiles and physical properties, indicating a link between genetic alterations and physical properties. Finally, the malignant cell-specific physical properties were confirmed by an HS-SICM using human colon cancer-derived cells. These results indicate that the HS-SICM analysis is useful as a novel diagnostic strategy for predicting the metastatic ability of cancer cells.